2014
DOI: 10.1371/journal.pone.0093849
|View full text |Cite|
|
Sign up to set email alerts
|

Amplicon –Based Metagenomic Analysis of Mixed Fungal Samples Using Proton Release Amplicon Sequencing

Abstract: Next generation sequencing technology has revolutionised microbiology by allowing concurrent analysis of whole microbial communities. Here we developed and verified similar methods for the analysis of fungal communities using a proton release sequencing platform with the ability to sequence reads of up to 400 bp in length at significant depth. This read length permits the sequencing of amplicons from commonly used fungal identification regions and thereby taxonomic classification. Using the 400 bp sequencing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 31 publications
(38 reference statements)
0
34
0
Order By: Relevance
“…However, the database for this gene is highly biased toward metazoans and may thus be limited in the detection of other groups (such as algae and unicellular eukaryotes). Other genes have been targeted for ecological studies (e.g., 18S rDNA, Logares et al, 2014a, 28S rDNA, Hirai et al, 2015, and the ITS region Tonge et al, 2014) and a combination of these genes and COI may give a more comprehensive assessment of diversity. In the future, molecular studies using ARMS may also investigate the functional ability of the assemblage using shotgun metagenomic techniques.…”
Section: Artificial Structures To Monitormentioning
confidence: 99%
“…However, the database for this gene is highly biased toward metazoans and may thus be limited in the detection of other groups (such as algae and unicellular eukaryotes). Other genes have been targeted for ecological studies (e.g., 18S rDNA, Logares et al, 2014a, 28S rDNA, Hirai et al, 2015, and the ITS region Tonge et al, 2014) and a combination of these genes and COI may give a more comprehensive assessment of diversity. In the future, molecular studies using ARMS may also investigate the functional ability of the assemblage using shotgun metagenomic techniques.…”
Section: Artificial Structures To Monitormentioning
confidence: 99%
“…This cutoff has not been systematically reviewed or shown to be appropriate for fungal ITS sequencing data. Tonge et al (2014) found that some fungi cannot be amplified by specific “conserved” primer pairs and suggested that a “multi-region approach be taken for other amplicon-based metagenomic studies”. This was not done in our study and may be a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing the microbial diversity using NGS can be achieved by using two different approaches 1) amplicon sequencing 2) shortgun metagenomics. In first approach the DNA fragments are amplified using a specific primer targeting a single gene like the 16S rDNA for eubacteria [55,56]. In second approach, the large DNA fragments or even complete genomes from organisms in a community can be characterized using shortgun libraries and amplifying them using multiple primer sets.…”
Section: Metagenomicsmentioning
confidence: 99%